A study of the patis industry in Manila and it's environment - Tesoro, Luz C.; Perez, Presentacion T. (1959.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Food industry and trade -- Philippines -- Manila